(untitled) (Universal International Scientific Journal, 2026)
This article is devoted to studying the effectiveness of the design thinking method in developing students’ scientific thinking using digital learning tools. The widespread use of digital technologies in the modern educational process creates opportunities for interactive, individual and distance learning. The study analyzes in detail the theoretical foundations of the design thinking method, its stages in the educational process, as well as its compatibility with digital tools. The article considers the possibilities of forming students’ creative, critical and analytical thinking through interactive platforms, virtual laboratories, simulations, online tests and electronic educational programs. The results of the study show that the use of the design thinking method with digital tools increases students’ ability to solve problems, conduct scientific research and develop innovative approaches. The article also provides criteria for assessing the effectiveness of the method, methods for its practical application in the educational process and recommendations for increasing student motivation. This study aims to identify effective strategies that serve to form scientific thinking and creative thinking in the modern educational system.